Effects of music therapy accompanied by transcranial direct current stimulation on the recovery from aphasia following stroke: A single‑center retrospective cohort study. (2022) - Aravantinou‑fatorou, Aikaterini; Georgakopoulou, Vasiliki Epameinondas; Spandidos, Demetrios A.
No abstract available